Gender differences in substance abuse, PTSD and intentional self-harm among veterans health administration patients. (1st February 2017) - Gradus, Jaimie L.; Leatherman, Sarah; Curreri, Andrew; Myers, Lisa G.; Ferguson, Ryan; Miller, Matthew
Highlights: Post-traumatic stress disorder (PTSD) and alcohol abuse/dependence interact to predict intentional self-harm (ISH) in female Veterans Health Administration (VHA) patients. PTSD and alcohol abuse/dependence interaction is weaker in male VHA patients. PTSD and drug abuse/dependence have a strong interaction predicting ISH in females. No interaction was found for PTSD and drug abuse/dependence in males. Abstract: Background: Epidemiologic studies have reported substance abuse and posttraumatic stress disorder (PTSD) diagnoses as risk factors for suicide among Veterans Health Administration (VHA) patients. Research on risk factors for suicide may not generalize to our understanding of non-fatal intentional self-harm (ISH), given the evidence that these outcomes have unique risk factors. The aims of this study were to examine (1) gender-stratified rates of non-fatal ISH in VHA patients with alcohol abuse/dependence, drug abuse/dependence, and PTSD and (2) gender-stratified interaction between alcohol abuse and dependence and drug abuse and dependence and PTSD in predicting non-fatal ISH. Methods: Participants include all VHA care users who received a PTSD diagnosis in Massachusetts from 2000 to 2008 (n = 16, 004) and an age- and gender-matched comparison group (n = 52, 502). Data were obtained from the VHA administrative registries. Results: We found evidence of stronger interactions between substance abuse diagnoses and PTSD in predicting non-fatal ISH for females than for males. The interaction contrast (IC) for alcohol abuse and dependence and PTSD in predicting non-fatal ISH among female VHA patients was 62.35/100, 000 person-years; for male VHA patients the comparable IC was 21.49/100, 000 person-years. For female VHA patients the IC for drug abuse and dependence and PTSD predicting ISH was 256.33/100, 000 person-years; no interaction was observed for male VHA patients. Conclusions: This study contributes to the scant literature on gender differences in substance abuse and PTSD among VHA patients. The findings highlight comorbid diagnoses as particularly important risk factors for non-fatal ISH among female VHA patients.